Finding Oneself in the Cosmic Dance: Nature's Grace for Thomas Merton - Weis, Monica (Cistercian studies quarterly, 2015)
The article presents a speech by author Monica Weis delivered at the Festival of Faiths, Louisville in Kentucky, on May 15, 2014. Topics of the speech included her spiritual insight on Thomas Merton, a Cistercian monk from the nearby Abbey of Gethsemani, the involvement of Merton on a cloistered monastery that would cut off his interaction with nature and the powerful spiritual lesson about the immense mercy of God.